Electron density distribution and electronic structure as tools to study the origin of ferroic states in ferroelectric and magnetic materials. (8th August 2016) - Santos, G. M.; Catellani, I. B.; Bini, R. D.; Perin, G. H.; Cótica, L. F.; Padilha, J. E.; Freitas, V. F.; Santos, I. A.; Guo, R.; Bhalla, A. S.
ABSTRACT: In this paper, three well-known prototypic ferroic materials, BaTiO3, PbZr0.4 Ti0.6 O3 and Fe3 O4, were experimentally and theoretically investigated to explore the origin of their respective ferroic state. Their structural properties were determined by X-ray powder diffraction and Rietveld refinement. The electron density distribution around cationic and anionic sites were obtained by using the Maximum Entropy Method on analyzing the X-ray diffraction results. Electron density distributions and the electronic band structures were determined by Density Functional Theory simulations using experimental and refined structural parameters as input data. The results show a strong correspondence for all the obtained properties and features, suggesting the important role of structural aspects and chemical bonding in the stabilization of the ferroic states in each studied system.